REFORMULATION OF ISLAMIC BOARDING SCHOOLS IN ATTRACTING THE SYMPATHY OF THE RELIGIOUS LEARNING COMMUNITY - Indah Aliyyah, Dini Asfarina; Mansur, Rosichin; Wiyono, Dwi Fitri (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2023)
This research aimed to describe the results obtained from the reformulation of the Ngalah Islamic Boarding School to attract the sympathy of the community to learn Islamic religious knowledge. This research used a qualitative approach that emphasizes the social processes that occur at the Ngalah Islamic Boarding School. In the data collection process that will be carried out, several data collection techniques are used (in-depth interviews, field observations, and documentation. Data analysis used interactive analysis, namely data collection, data simplification, data presentation and conclusion submission. The results of the research showed that the reformulation used by The Ngalah Islamic Boarding School included: 1) kyai figures; implementation of Kyai's dawuh as the basis of Islamic boarding schools, 2) Holding regular recitations for the general public, 3) preparing books and distributing them for free or for a fee, 4) Islamic boarding school alumni forming the IKSAN organization, 5) complete educational facilities through development activities, improvements and management programs, maintenance and development of facilities. 6) pluralism and multiculturalism by instilling these values, whether written in the curriculum or not, and in real practice.